Nursing Assessment in Intensive Care Unit: A Systematic Review - Safrullah Safrullah; Tintin Sukartini; Erna Dwi Wahyuni (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nursing assessment in critical patients in the ICU is a complex process that is essential for supporting standard interventions to improve the safety and quality of nursing care. This study aims to identify and analyze various literature related to nursing assessments and nursing care based on ICU service standards. A total of 293 articles were initially identified from various databases: 52 from PubMed, 145 from ScienceDirect, 83 from Google Scholar, 10 from Scopus, and 3 from ProQuest. After removing 85 duplicate articles, 208 articles remained. The screening process based on title identification, further reduced 55 articles. Subsequent abstract screening yielded 31 articles. Finally, a full text review of these articles resulted in 10 articles selected for inclusion. The literature review found that pre-arrival assessments help prepare for patient care needs before ICU arrival. Quick checklist based assessments can quickly and systematically identify early critical conditions in patients. Comprehensive assessments, using an integrated and ongoing patient assessment format, combined with progress notes and sophisticated monitoring tools, can enhance the efficiency of patient care. The conclusion is that implementing Nursing Assessment through a systematic approach to ICU services significantly contributes to optimizing the quality and safety of critical patient care.